Cross Culture Understanding in English Camp Program 2019: An Islamic Perspective from Madurese College Students - Iin Rachmawati (Sosial Budaya, 2019)
The term cross cultural understanding had long been known by many people all over the world, but only a few of them knows about the influence of Islamic values along with the cross cultural understanding theme in an event called English Camp Program 2019. Due to that reason, the researcher is interested in digging more about how the Islamic values of Madurese college students affect their understanding about cultural differences of English-speaking countries in English Camp Program. In general, this research will use qualitative descriptive method because the main goal is to describe about those college students’ understanding on cultural differences in relation with Islamic values on students’ background. The result of this research shows that those Madurese college students are still holding on their Islamic values which are coming from their religious background when it comes to understand about cultural differences happened in certain English-speaking countries during the English Camp Program. Also, their Islamic values are not blocking or limiting their openess about receiving some cultural differences happened all over the world.